(untitled) (Journal of the Management Sciences, 2025)
Tax authorities across the world have struggled with the question of why people voluntarily comply with tax laws. To have a better insight into the phenomena, this study explores how religiosity, moral reasoning, perception of government and peer influence affects voluntary tax compliance behaviour of self-employed. Surveying 367 self-employed individuals, the results of regression analysis showed that religiosity and peer influence have significant positive impact on voluntarily tax compliance. However, the finding of the study revealed that moral reasoning and perception of government have no significant impact on voluntary tax compliance. This study recommends that government should also engage in massive campaign that will highlight the importance of paying taxes to individuals and also emphasises the religious injunctions on tax evasion since level of religiosity was found to have an influence on voluntary tax compliance behaviour.